Velvet beans help maize farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Farmers in small villages on the north coast of Honduras are using velvet bean in association with their maize crops and obtaining good results m terms of yield increases, protection of soils from erosion and reduction of weeding. The velvet bean...